Exchange Rate Policy Regimes, Private Investment Behaviour and Economic Growth in Nigeria (1960 -2020) - Mufutau Akanmu Popoola; Jimoh Olayinka Ajayi; Tijani Saheed Abiodun (Financial Markets, Institutions and Risks)
To improve economic growth acceleration, the Nigerian government should continue to formulate and implement several policies including exchange rate policy regimes. Exchange rate policy regime of any government could be a fixed exchange rate regime when the price of a country’s currency in terms of another country’s currency is fixed to a value by the monetary authority; it could be a floating regime when the price of a country’s currency in terms of another country’s currency is left to be determined by the forces of demand and supply, while a managed-floating regime is undertaken when there is an element of both fixed and floating regimes. Following the Barro (1990) theoretical framework, this study attempted to assess the effects each exchange rate regime has on the economy through the mechanism of private investment spending. The researcher carefully selected macroeconomic variables that have been considered in the econometric models for empirical analysis of the research study in this dissertation through statistical estimation techniques as guided by Barro (1990) and international studies, specifically that of Sahoo et al., (2012), in this area of study. These variables include GDP as an indicator for economic growth, Private capital, private sector credit, real exchange rate, interest rate, government capital expenditure, trade openness, exchange rate regimes dummies, total employment, and spending on health and education. Specifically, the study set out to empirically quantify the impact of both fixed and floating regimes on private investment spending and in turn, on economic growth in Nigeria.Through this study, the key determinants of private investment spending and economic growth in Nigeria. To achieve the study’s objectives and address the respective research questions, preliminary examinations of the data were conducted through the use of visual and unit root tests and some of the variables were found to be stationary at levels (i.e., /(0)) while some are stationary in their first differences (i.e., /(1)). The study proceeded to estimate both private investment and economic growth models simultaneously using Two-Stage Least Squares (TSLS) method.